Factors Influencing on Quality of Life: Model Selection by AIC - Thi Ngan, Nguyen (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to identify the factors that influenced the Quality of Life. Survey data were collected from 268 respondents living in HCM City, Vietnam. The research model was proposed from the studies of Quality of Life. Cronbach’s Alpha evaluated the reliability and validity of the scale. The model selection of AIC showed that Quality of Life was impacted by the six components of the Quality of Life included economic condition, governance, health, housing, participation in culture, leisure and community, and quality of the environment.